Design-centered entrepreneurship - Basadur, Min; Goldsby, Michael G.; Mathews, Rob (Professor of management) (Routledge, 2022)
"Grounded in extensive research and field-testing, Design-Centered Entrepreneurship presents a concise, problem-solving approach to developing a unique business concept. Step-by-step guidelines provide insight into exploring market problem spaces, uncovering overlooked opportunities, reframing customer problems, creating business solutions, and sustaining success and an entrepreneurial culture. Drawing on methodologies from the world of design, the book helps students of entrepreneurship to fill in the missing piece that transforms opportunity recognition into a viable business concept. Plenty of useful diagrams help to organize key concepts, making them easily accessible to readers. This second edition has been updated to include social entrepreneurship, more international examples and enhanced support materials. The digital supplements include a virtual Creative Problem Solving Profile, slides and an instructor manual. Design-Centered Entrepreneurship is the ideal text for entrepreneurship and new venture creation courses with a focus on design thinking"--